PROPOSED STRATEGIC PLANS FOR RIDE-HAILING COMPANY TO ACCELERATE THE TRANSITION TO ELECTRIC VEHICLES - Yoga Wicaksono, Tristantyo
By the signing of the Paris Agreement in 2015, countries pledged to reduce their greenhouse gas emissions to prevent and mitigate global warming. The Paris Agreement is different from any other because companies, or non-state actors, were also advocates in favor of a strong deal. Businesses will play a major part in the success of the agreement. The government of Indonesia has shown its commitment to support this agreement by signing and ratifying the 2015 Paris Agreement through Law No. 16 of 2016. The government of Indonesia set some strategies to achieve net zero emissions by 2060, and one of them is by pushing the utilization of electric vehicles. The transportation sector which has a heavy reliance on fossil fuels, made up the largest share of Indonesia’s end-use energy demand and is projected to reach almost 2.5 times today’s energy consumption by 2050. Indonesia has shown an interest in reducing its dependency on fossil fuels and transitioning towards electric vehicles. To push the development of Electric Vehicle (EV) industry in Indonesia, the government has taken some initiatives to issue supporting policies and incentives. OJOL is a tech company that offers a range of services including ride-hailing services. OJOL has committed to managing and reducing its carbon footprint by launching a Carbon Offsetting Program, one of the contents of which is transitioning its fleet to EVs, including Electric 2-wheeler, as a strategy to reduce carbon footprints. However, since it is being launched, the implementation of the program is going slowly. Besides the internal capabilities of OJOL, the success of this program is also very dependent on external factors. To determine the strategic plans, the root-cause needs to be identified first. And then the business conditions will be analyzed internally and externally to determine the strengths, weaknesses, opportunities, and threats that OJOL has. Furthermore, the points that are determined from business condition analysis will be used as the base to develop strategic plans to solve the problems that OJOL has.